Measuring Reading Difficulty Using Lexile Framework And Gunning Fog Index - Christanti, Viny; Naga, Dali S.; Benedicta, Cheria (Teknik dan Ilmu Komputer, 2017)
This article describes the development of readability measuringÃÂ  tools for Indonesian Text by using Lexile Framework, Gunning Fog Index, and Cloze Test. Lexile Framework and Gunning Fog Index are used in English Text and are implemented to Indonesian Text. Lexile Framework measures the difficulty level of the text by using the text itself and other readingsÃ¢â¬â¢ frequencies as reference parameters, while the Gunning Fog Index uses the text itself as parameter. LexileÃÂ  Framework is implemented to Indonesian by using a corpus of Indonesian, while the Gunning Fog Index is implemented to Indonesian by changing the rule in defining difficult words. The rule depends on the syllables of the words contained in the text with the addition of stemming process. Cloze Test is needed for comparing the measurement results. The result showed that the three methods of measurement have different values. Lexile logit requires some adjustments and a very large corpus, Gunning Fog Index needs improvement in stemming and cutting syllables, Cloze Test is needed on all readings and requires more respondents.ÃÂ Keywords: Taraf Sukar Bacaan, Lexile Framework, Gunning Fog Index, Cloze Test